(untitled) (Communication & Society, 1994)
The author explains the reasons that led the French Government to legislate in the advertising sector and to enact the law bearing his name, which the author – naturally – defends: the need for transparency, the deplorable operations of agencies and buying services, the lack of concordance and trust, the difficult general economic context, the need for drastic reform, etc.